2014
DOI: 10.1158/1078-0432.ccr-13-1517
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Germline Variant in GLI1 Implicates Hedgehog Signaling in Clinical Outcome of Stage II and III Colon Carcinoma Patients

Abstract: Purpose: Cumulating evidence indicates that germline variants in the Wnt, Notch, and Hedgehog pathways are involved in colon carcinoma progression and metastasis. We investigated germline polymorphisms in a comprehensive panel of Wnt, Notch, and Hedgehog pathway genes to predict time to recurrence (TTR) and overall survival in patients with stage II and III colon carcinoma.Experimental Design: A total of 742 consecutively collected patients with stage II and III colon carcinoma were included in this retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…DGT inhibits osteosarcoma growth and metastasis through repression of the HH/Gli1 pathway The protein Gli1 functions as a downstream transcription factor of HH signaling and plays a pivotal role in cellular growth and metastasis of many types of tumors (27)(28)(29). However, the function of Gli1 in osteosarcoma remains unclear.…”
Section: Dgt Suppresses Osteosarcoma Cell Metastatic Potential Both Imentioning
confidence: 99%
“…DGT inhibits osteosarcoma growth and metastasis through repression of the HH/Gli1 pathway The protein Gli1 functions as a downstream transcription factor of HH signaling and plays a pivotal role in cellular growth and metastasis of many types of tumors (27)(28)(29). However, the function of Gli1 in osteosarcoma remains unclear.…”
Section: Dgt Suppresses Osteosarcoma Cell Metastatic Potential Both Imentioning
confidence: 99%
“…53 Finally, Gli1 polymorphisms could predict for time to recurrence. 52 Nevertheless, in a number of studies these observations could either not be confirmed 32,43,54 or conflicting results were noticed. 50 One possible explanation for this might be differences in the populations studied.…”
Section: Discussionmentioning
confidence: 99%
“…In the reported studies where patients underwent resection for colon cancer, 32,[37][38][39]42,49,50,52,[38][39][40]43,50,[52][53][54] the administration of adjuvant chemotherapy was confirmed in only 3 of them. 43,52,54 Interestingly, pathway activation did not predict for survival in any of the studies in which patients received adjuvant chemotherapy. The small number of patients 32,50 and the evaluation of cytoplasmic rather than the nuclear expression of Gli1 43 could also contribute to these discrepancies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations